Wish I were here - Wiesner, Melissa (Forever, 2024)
"For type-A mathematician Catherine Lipton, growing up with a free-spirited single dad was more than a little stressful. So as an adult, everything in her life is ordered, from her lists to her lesson plans at her new job as a college professor. Catherine's carefully calculated life goes awry, though, when the university's human resources system rejects her employment paperwork. Soon after, her credit card is declined. At the social security office, Catherine makes a shocking discovery-she's disappeared from all government records, and there's no evidence she exists at all. Catherine can't seem to convince anyone she's a real person, even though she's standing right there in the flesh. The only person who offers to help is Luca Morelli, her attractive but aggravating doorman who spends more time flirting with Catherine's elderly neighbors than he does enforcing the building rules. But left with no other options, Catherine reluctantly agrees to enlist the help of Luca's well-connected Italian family. Soon, Catherine finds herself following Luca into the back room of a smoky bar to meet a man named Vito, breaking into the records room of a local hospital, and having a surprising amount of fun. She also finds herself growing closer to Luca, who makes her laugh and challenges her in ways she never expected. As Catherine begins to unravel the mystery behind her missing identity, she may discover that the "real" Catherine is someone she never expected"--